DCLK1 phosphorylates the microtubule‐associated protein MAP7D1 to promote axon elongation in cortical neurons. Issue 4 (24th November 2016) - Koizumi, Hiroyuki; Fujioka, Hiromi; Togashi, Kazuya; Thompson, James; Yates, John R.; Gleeson, Joseph G.; Emoto, Kazuo
ABSTRACT: Doublecortin‐like kinase 1 (DCLK1) is a member of the neuronal microtubule‐associated doublecortin (DCX) family and functions in multiple stages of neural development including radial migration and axon growth of cortical neurons. DCLK1 is suggested to play the roles in part through its protein kinase activity, yet the kinase substrates of DCLK1 remain largely unknown. Here we have identified MAP7D1 (microtubule‐associated protein 7 domain containing 1) as a novel substrate of DCLK1 by using proteomic analysis. MAP7D1 is expressed in developing cortical neurons, and knockdown of MAP7D1 in layer 2/3 cortical neurons results in a significant impairment of callosal axon elongation, but not of radial migration, in corticogenesis. We have further defined the serine 315 (Ser 315) of MAP7D1 as a DCLK1‐induced phosphorylation site and shown that overexpression of a phosphomimetic MAP7D1 mutant in which Ser 315 is substituted with glutamic acid (MAP7D1 S315E), but not wild‐type MAP7D1, fully rescues the axon elongation defects in Dclk1 knockdown neurons. These data demonstrate that DCLK1 phosphorylates MAP7D1 on Ser 315 to facilitate axon elongation of cortical neurons. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 77: 419–437, 2017